Pengaruh Pemberian Beberapa Dosis Pupuk (N, P, K ) dan Jenis Pupuk Alternatif terhadap Hasil Tanaman Padi (Oryza sativa L.) dan Kadar N, P, K Inceptisol Selemadeg, Tabanan - KASNIARI, D.N.; SUPADMA, A.A.NYOMAN (AGRITROP; Vol. 26, No. 4 Desember 2007, 2012)
A pot experiments was conducted in September 2000 until January 2001 at Experimental Station of Faculty of Agriculture, Udayana University. The experiment was arranged in Completely Randomized Design with treatments allocation in factorial with three replications. The treatments were : the first factors consisted of four rates of N,P,K fertilizers: F1 = 300 kg Urea, 75 kg SP.36, 50 kg KCl ha-1 (1.2 g Urea, 0.3 g SP.36, 0.2 g KCl pot-1) ; F2 = 250 kg Urea, 50 kg SP.36, 25 kg KCl ha-1 (1.0 g Urea, 0.2 g SP.36, 0.1 g KCl pot-1) ; F3 = 200 kg Urea, 25 kg SP.36, 0 kg KCl ha-1 (0.8 g Urea, 0.1 g SP.36, 0 g KCl pot-1); F4 = 150 kg Urea, 0 kg SP.36, 0 kg KCl ha-1 (0.6 g Urea, 0 g SP.36, 0 g KCl pot-1). The second factors were three kind of alternative fertilizers : Fr (Floran), Gn (Greener) and Dg (Dekorgan) each rate 3 l ha-1 or 1.333 ml pot-1 (concentrations 3 ml l-1 water). The results indicated that the interactions between fertilizers rates (N,P,K) with kind of alternative fertilizers were not significantly different for all variable observed. The alternative fertilizers not significantly different for all variable too but fertilizers rates (N,P,K) affected the fertile number of rice tillers and highly significantly affected to the available P and K in the soil. The treatment of 250 kg Urea, 50 kg SP.36, 25 kg KCl ha-1 gave the highest fertile tillers (37.00 tillers pot-1) and available P in soil (10.18 ppm) but the treatment of 300 kg Urea, 75 kg SP.36, 50 kg KCl was observed the highest available K in the soil. The combination treatment of 300 kg Urea, 75 kg SP.36, 50 kg KCl ha-1 with Dekorgan produced the highest rice yield (65.69 g pot-1) or 58.14 % higher than the lowest yield produced by combination treatment between 200 kg Urea, 25 kg SP.36, 0 kg KCl ha-1 and Dekorgan.
Keywords: (N, P, K), Alternative Fertilizers, Oryza sativa L., Inceptisols